Serpin B9 is Highly Expressed in Lung Adenocarcinoma and is Associated with Progression-Free Survival - Fang Y; Yue Y; Hao S; Zhang Y; Liu N; Wang S; Li Y; Wang H (Dove Medical Press, 2024)
Yue Fang,1,2,* Yi Yue,3,* Sensen Hao,1 Ying Zhang,4 Nan Liu,1 Shengling Wang,1 Yan Li,1 Hongzhi Wang1 1Galactophore Oncology Center, Hefei Cancer Hospital, Chinese Academy of Sciences, Hefei City, Anhui Province, People's Republic of China; 2Science Island Branch, Graduate School of University of Science and Technology of China, Hefei City, Anhui Province, People's Republic of China; 3The Second Clinical College, Anhui Medical University, Hefei City, Anhui Province, People's Republic of China; 4Department of Pathology, First Affiliated Hospital of Anhui Medical University, Hefei City, Anhui Province, People's Republic of China*These authors contributed equally to this workCorrespondence: Hongzhi Wang, Email wanghz@hfcas.ac.cnBackground: Serpin B9 is highly expressed in breast cancer, melanoma, and various malignant cells and inhibits NK cell killing through the Serpin B9-GrB axle. However, the current studies have only validated the role of Serpin B9 in vivo and vitro, and lack of systematic studies on the expression of Serpin B9 in patients' tumor tissues and its prognostic implications. In this study, we propose to further validate the role of Serpin B9 by comparing its expression level in tissues of lung adenocarcinoma patients and its correlation with the efficacy of immunotherapy.Methods: This study included 200 patients with LUAD between Feb 2022 and Feb 2023. IHC scoring assessed Serpin B9 expression in the tumor and adjacent tissues, with an H-score of 2 as the cutoff value. Patients were divided into high- and low-expression groups. T-tests were used to compare Serpin B9 expression and treatment efficacy between the tumor and adjacent tissues in both groups. Baseline characteristics were compared using X2 tests. Prognostic risk factors were identified using Cox regression and Kaplan-Meier survival curves.Results: The expression level of Serpin B9 in LUAD tumor tissues are higher than adjacent tissues and positively correlated with the TNM stage and negative correlated with PFS in patients with LUAD. Additionally, immunotherapy efficacy was inversely correlated with Serpin B9 expression.Conclusion: The increased expression of Serpin B9 in LUAD tumor tissues is negatively linked to prognosis and immunotherapy efficacy. This underscores their potential as prognostic and therapeutic targets.Keywords: serine proteinase inhibitor B9, lung adenocarcinoma, progression free survival, PD-1/PD-L1